Risk Factors of Saudi Asthmatic Patients Less Than 12 Years Old in Maternity and Children’s Hospital - Majed Ahmed Almogbel, Nasser Mesfer Rashed Al-abataheen, Rakan Jamel Al sahagi; Abdulaziz Abdulla Alshehri, Faisal Tahir Mohmood, Rasha Ali Ahmed Abuandoos; Abdulmajeed M Bajunaid, Hassan Nasser Alkahtani, Abdulaziz Abdullah Alsharif; Yousef Hussain Almakrami, Ibrahim Hassan Abu saq, Ali Khalid M Alsharif (International Journal of Innovative Research in Medical Science, 2017)
Asthma is a common chronic inflammatory disease of the airways characterized by variable and recurring symptoms, reversible airflow obstruction and bronchospasm, and it can be divided into extrinsic-implying a definite external cause and intrinsic - when no causative agent can be identified. The extrinsic type starts in childhood. Facility- based descriptive case series study including qualitative research approaches study will be conducted in Maternity and Children's Hospital to identify the common risk factor that lead to bronchial asthma among children's. Sampling by selective sampling techniques will be using for the selection of 50 Saudi asthmatic files for children's less than 12 year old. The data will be collected by structured interview questionnaire (multiple choice questions), the check lists. Data processing and analysis will be done by entering the data into SPSS for Windows. After analysis of data exposed that the genetic has a relationship with the bronchial Asthma disease as it affect 70% of asthmatic children and just 30% are not affected, the chronic obstructive pulmonary disease are commonly seen in asthmatic children as it affect 66%,while not found in 34%, the nocturnal asthma are absent in 20%, occur 1 to 2 times per week in 46%and 4 or more times per week in 34%, The environmental affect 76% and not affect 24% of asthmatic children in maternity and children's hospital, the exercise exacerbated asthma in 70% and not exacerbated in 30%, the affect of paracetmol and beta blocker on asthmatic children's in maternity and children hospital with 80% are affected, while 20% not affected.